Comparison of the efficacy and safety of rosuvastatin versus atorvastatin in reduction of low density lipoprotein cholesterol in patients of type 2 diabetes mellitus with dyslipidemia - Kashyapa, Hrishikesh; Jadhav, Rupali Bajrang; Deshkar, Anuradha (International Journal of Research in Medical Sciences, 2018)
Background: Approximately 80% of deaths in diabetic patients are attributable to cardiovascular disease (CVD), which in turn is highly correlated with diabetic dyslipidemia. Statins are drug of choice for raised LDL-C in treating dyslipidemia. The present study compares the efficacy and safety of rosuvastatin against commonly used atorvastatin in patients of type 2 diabetes mellitus with dyslipidemia, so as to guide the present treatment strategies in the management of the same in Indian population. Methods: The study was a single blinded study conducted in a district level tertiary care hospital attached to a medical teaching institute. Patients fulfilling the inclusion criteria were randomized in two groups. Group I received atorvastatin (10mg) and group II received rosuvastatin (5mg) at bedtime orally daily. Serum TC, serum LDL-C, serum HDL-C and serum TG were assessed on week 0, week 6 and week 12. Results: At the end of 12 weeks, the percentage reduction of LDL-C levels in atorvastatin group was 33.58% whereas in rosuvastatin group, it was 43.12%. The percentage reduction in total cholesterol (TC) in atorvastatin group was 24.85% while in rosuvastatin group, it was 30.8%. Rise in HDL-C levels in atorvastatin group was 7.1% whereas in rosuvastatin group, it was 11.16%. All these differences were statistically significant. There was no significant difference in reduction of TG levels between the two groups. Conclusions: Rosuvastatin 5mg causes greater reduction in LDL-C and TC, comparable reduction of TG and greater rise in HDL-C when compared with atorvastatin 10mg therapy.